2020
DOI: 10.3390/healthcare8030204
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for International Cooperation in the COVID-19 Pandemic Era: Focusing on National Scientific Funding Data

Abstract: The coronavirus crisis may lead to a deeper understanding of international collaborations for developing antivirals and vaccines that are essential to protect us from current and future health security threats. Beyond technical solutions, the government of South Korea needs to establish a timely strategic investment in coronavirus-related research and development (R&D) in order to enhance the capabilities for managing this new uncertainty in regard to the domestic health crisis. Thus, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…All nodes in the network were displayed based on the titles of the research fields present in the ASJC codes, and the font size was presented based on the frequency of the co-occurrence of each ASJC code in comparison with the other codes. By visualizing this network structure, we can figure out the relationship between the ASJC codes [ 33 , 34 ]. In this study, we used the modularity-based clustering method from VOSviewer (Leiden University, Leiden, The Netherlands, Version 1.16.15) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…All nodes in the network were displayed based on the titles of the research fields present in the ASJC codes, and the font size was presented based on the frequency of the co-occurrence of each ASJC code in comparison with the other codes. By visualizing this network structure, we can figure out the relationship between the ASJC codes [ 33 , 34 ]. In this study, we used the modularity-based clustering method from VOSviewer (Leiden University, Leiden, The Netherlands, Version 1.16.15) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Ng [42] observed that traditional Chinese medicine and vitamin D were often mentioned as alternative therapies before the introduction of any medication or vaccine. Lee et al [20] determined the major research areas of studies supported by public funds in the United States, the European Union, Japan, and South Korea, and analyzed the characteristics of each country. This study observed that in South Korea, research mostly focused on immune reaction platforms, vaccine development, and diagnosis, and thereby inferred the South Korean government's development policies for biotechnology industries and the impacts of government-led research and development.…”
Section: Research Trends On Covid-19mentioning
confidence: 99%
“…Based on previous studies [51,52,54,55], a co-occurrence technique was employed to identify the hydrogen-economy-related research fields. The number of times the ASJC codes appeared together in a project group revealed the relevance of that project.…”
Section: Clustering Processmentioning
confidence: 99%
“…By visualizing this network structure, the relationship between the ASJC codes could be elucidated. The mapping and clustering were calculated based on previous studies [51,52,54,55].…”
Section: Clustering Processmentioning
confidence: 99%